Nomina Appellativa as Proper Names of Literary Characters – Spelling Issues - Ruszkowski, Marek (Respectus Philologicus, 2019)
[full article in Polish, abstract in English and Polish]The article deals with the problem of spelling common names functioning as proper names of literary characters. In general, single word names pose no problems as they are written in capital letters, e.g. Sędzia, Wojski, Asesor, Podkomorzy, Woźny, Hrabia (characters from “Pan Tadeusz”); Cześnik, Rejent (characters from “Zemsta”); Pustelnik (figures from “Dziady”). Definitely less clear is the usage and rule in terms of spelling that applies to names composed of two and more words, such as KRÓLOWA ŚNIEGU, MAŁY KSIĄŻĘ, ŚPIĄCA KRÓLEWNA, KRÓLEWNA ŚNIEŻKA, KOT W BUTACH, STAROSTA GADULSKI, PAN KLEKS. There are three versions of spelling as far as usage is concerned: 1) both words in capital letters, 2) the first word in capital letters, the second word in lower case, 3) both words in lower case. Much depends on the form in which the expression appears in the literary text and in its possible translation into Polish. Proper names in literary works are the result of the author’s choice, and this does not contribute to the unification of their spelling form (the same name of a character may be written differently in different works). If the author’s intentions are not known, we should recommend that all words (except for conjunctions and prepositions) be spelt in capital letters, especially as the other components of these expressions may appear in their own context: Książę, Śnieżka, Królewna.
Keywords: common names; proper names; spelling